2019
DOI: 10.1111/1440-1681.13098
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of PTPN18 can inhibit proliferation and metastasis and promote apoptosis of endometrial cancer

Abstract: Endometrial cancer is one of the chief culprits threatening women's lives. Although numerous epidemiological experiments have been carried out into the aetiology of endometrial cancer, the cause of the disease has been unclear up to now. In recent years, PTPN18, a member of the protein tyrosine phosphatases (PTP) family predicted to be tumour suppressors or oncogenes, has been confirmed to participate in the occurrence and progression of many cancers. Few studies, however, have explained the role in the endome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Previous studies have demonstrated that PTPN18 is a tumor suppressor in breast cancer 29 and hepatocellular carcinoma, 30 while PTPN18 overexpression can promote the development of endometrial cancer. 23 In addition, different PTPs exert different functions in CRC. Specifically, PTPN4, 31 PTPN9, 32 and PTPRT 33 act as tumor suppressors in CRC, while PTPN2 34 can promote tumor development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that PTPN18 is a tumor suppressor in breast cancer 29 and hepatocellular carcinoma, 30 while PTPN18 overexpression can promote the development of endometrial cancer. 23 In addition, different PTPs exert different functions in CRC. Specifically, PTPN4, 31 PTPN9, 32 and PTPRT 33 act as tumor suppressors in CRC, while PTPN2 34 can promote tumor development.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 , 22 However, recent studies have shown that PTPN18 knockdown can inhibit the proliferation of tumors and promote apoptosis in endometrial cancer. 23 …”
Section: Introductionmentioning
confidence: 99%
“…Protein tyrosine phosphatase nonreceptor type 18 (PTPN18) is the first discovered specific tyrosine phosphatase of human epidermal growth factor receptor 2 (HER2), which is closely linked to tumor development [13,14]. Protein tyrosine phosphatases influence cell growth and other cellular functions under external stimuli [13].…”
Section: Introductionmentioning
confidence: 99%
“…PTPN18 negatively regulates HER2 tyrosine kinase activity mainly through selectively dephosphorylating the tyrosine phosphorylation site of HER2, thereby effectively regulating cell function [13]. Previous evidence reported the expression of PTPN18 in kinds of tumor cell lines [13,14]. In addition, it is able to inhibit the progression of chronic myeloid leukemia and to influence functions of hematopoietic stem cells [13,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis is a new type of tumor cell death, which plays an important role in multiple cancers [ 14 ]. PTPN18 is considered to serve as an oncogene in endometrial cancer, which promotes proliferation and metastasis of endometrial cancer cells [ 15 ]. Another study revealed that silencing of PTPN18 could induce ferroptosis by inhibiting GPX4 activity, leading to the suppression of endometrial cancer cell growth [ 16 ].…”
Section: The Roles Of Ferroptosis In Cancersmentioning
confidence: 99%